2004
DOI: 10.1063/1.1833552
|View full text |Cite|
|
Sign up to set email alerts
|

Continuous liquid crystal pretilt control through textured substrates

Abstract: Reliable control on the pretilt alignment of nematic liquid crystal (LC) in the 30°-50°range is a well-known challenge. An unconventional approach, involving microtextured surfaces with domains favoring dissimilar LC alignments, has recently demonstrated applicability in bi-and tristable displays. These textured domains realize the so-called frustrated boundary condition in which the LC elastic energy built-up (frustration) can drive the LC alignment into macroscopic uniformity. Here we show that one can harne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Kim et al [18][19][20] presented a general approach to establishing in-plane alignment bistability by exploiting the orientational frustration induced by a checkerboard pattern. Lee et al [21] subsequently demonstrated a continuous variation in LC pretilt using a checkerboard pattern comprising regions with orthogonally etched grooves. Bechtold and Oliveira [22] experimentally investigated the equilibrium configuration of the director for a submicron patterned substrate, creating alternating homeotropic and random planar stripes by selectively irradiating a SAM with deep UV.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [18][19][20] presented a general approach to establishing in-plane alignment bistability by exploiting the orientational frustration induced by a checkerboard pattern. Lee et al [21] subsequently demonstrated a continuous variation in LC pretilt using a checkerboard pattern comprising regions with orthogonally etched grooves. Bechtold and Oliveira [22] experimentally investigated the equilibrium configuration of the director for a submicron patterned substrate, creating alternating homeotropic and random planar stripes by selectively irradiating a SAM with deep UV.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, topographically or chemically patterned surfaces permit essentially arbitrary control of the easy axis and anchoring potential through appropriate adjustment of the pattern features [1]; suitable patterning techniques include atomic force microscope scribing of polymer films [2,3], microcontact printing of self-assembled monolayers (SAMs) [4][5][6], and photolithography [7][8][9][10]. By imprinting a design of appropriate symmetry, it is also possible to pattern a surface to promote more than one stable alignment orientation [2,[11][12][13][14] thus enabling the fabrication of bistable devices [2,10,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The method to increase the pretilt angle for the surface patterning process for LC alignment is divided into two aspects, the groove-shape design [21,40] and the formation of physically or chemically inhomogeneous textures. [17,41,42] However, because the groove-shape design and physically inhomogeneous texture are difficult to apply to nanometer-scale structures with better optical performance and it is difficult to know the exact LC transition direction, the chemically inhomogeneous texture is the appropriate method to increase the pretilt angle and ensure a fixed LC direction and good optical properties. Therefore, we will now proceed to investigate the increase of the pretilt angle by the formation of the chemically inhomogeneous texture and this will be described in future reports.…”
Section: Lc Alignment and Pretilt Formationmentioning
confidence: 99%